Radiosensitizing capacity of fenofibrate in glioblastoma cells depends on lipid metabolism - Bayan Alkotub; Lisa Bauer; Ali Bashiri Dezfouli; Khouloud Hachani; Vasilis Ntziachristos; Gabriele Multhoff; Morteza Hasanzadeh Kafshgari (Redox Biology)
Despite advances in multimodal therapy approaches such as resection, chemotherapy and radiotherapy, the overall survival of patients with grade 4 glioblastoma (GBM) remains extremely poor (average survival time <2 years). Altered lipid metabolism, which increases fatty acid synthesis and thereby contributes to radioresistance in GBM, is a hallmark of cancer. Therefore, we explored the radiosensitizing effect of the clinically approved, lipid-lowering drug fenofibrate (FF) in different GBM cell lines (U87, LN18). Interestingly, FF (50 μM) significantly radiosensitizes U87 cells by inducing DNA double-strand breaks through oxidative stress and impairing mitochondrial membrane integrity, but radioprotects LN18 cells by reducing the production of reactive oxygen species (ROS) and stabilizing the mitochondrial membrane potential. A comparative protein and lipid analysis revealed striking differences in the two GBM cell lines: LN18 cells exhibited a significantly higher membrane expression density of the fatty acid (FA) cluster protein transporter CD36 than U87 cells, a higher expression of glycerol-3-phosphate acyltransferase 4 (GPAT4) which supports the production of large lipid droplets (LDs), and a lower expression of diacylglycerol O-acyltransferase 1 (DGAT1) which regulates the formation of small LDs. Consequently, large LDs are predominantly found in LN18 cells, whereas small LDs are found in U87 cells. After a combined treatment of FF and irradiation, the number of large LDs significantly increased in radioresistant LN18 cells, whereas the number of small LDs decreased in radiosensitive U87 cells. The radioprotective effect of FF in LN18 cells could be associated with the presence of large LDs, which act as a sink for the lipophilic drug FF. To prevent uptake of FF by large LDs and to ameliorate its function as a radiosensitizer, FF was encapsulated in biomimetic cell membrane extracellular lipid vesicles (CmEVs) which alter the intracellular trafficking of the drug. In contrast to the free drug, CmEV-encapsulated FF was predominantly enriched in the lysosomal compartment, causing necrosis by impairing lysosomal membrane integrity. Since the stability of plasma and lysosomal membranes is maintained by the presence of the stress-inducible heat shock protein 70 (Hsp70) which has a strong affinity to tumor-specific glycosphingolipids, necrosis occurs predominantly in LN18 cells having a lower membrane Hsp70 expression density than U87 cells.In summary, our findings indicate that the lipid metabolism of tumor cells can affect the radiosensitizing capacity of FF when encountered either as a free drug or as a drug loaded in biomimetic lipid vesicles.